Demographic and socioeconomic differences in consumption of sugar-sweetened beverages among colombian children and adolescents (2015)
Introduction: sugar-sweetened beverages (SSB) are becoming a common component in the diets among children and adolescents, and its consumption is associated with an increased risk factors for cardiovascular disease. The aim of the present study was to describe the consumption of sugar-sweetened beverages among Colombian children and adolescents and to examine whether differences by demographic and socioeconomic according to gender. Methods: we used data from the 2010 National Nutrition Survey of Colombia (ENSIN 2010) for 10 373 children and adolescents between 5 and 17 years old. SSB intake was based on intake from regular soda and/ or concentrated drinks. Demographic factors (sex, age, ethnicity, urbanicity, area and geographic region) and socioeconomic level (social class) were collected by structured questionnaire. Associations were established through a multivariate logistic regression. All analyzes were calculated by complex samples. Results: nationwide, 23% of girls and 22.4% of boys drank SSB at least once a week. Differences by demographic factors were observed for SSB consumption. In girls, factors associated with a greater odds for SSB intake (? 1 time/week) were aged 14 to 17 years old [OR = 1.65 (95%CI = 1.32, 2.06)], living in the central region [OR = 2.42 (95%CI = 1.81, 3.25)] and urban area [OR = 1.77 (95%CI = 1.42, 2.20)]. In boys, the multivariate logistic regression shows that adolescents aged 14 to 17 years old [OR = 1.96 (95%CI = 1.58, 2.24)], living in the national territories (South) [OR = 2.42 (95%CI = 1.77, 3.32)] and urban area [OR = 1.79 (95%CI = 1.45, 2.20)] were associated with a higher probability of SSB consumption. Social class was not associated with SSB intake. Conclusions: SSB intake varies by certain demographic factors. Government can use findings from this study to tailor efforts to decrease SSB intake and to encourage consumption of more healthful beverages (e.g, water) among Colombian children and adolescents Conclusions: SSB intake varies by certain demographic factors. Government can use findings from this study to tailor efforts to decrease SSB intake and to encourage consumption of more healthful beverages (e.g, water) among Colombian children and adolescents © 2015, Grupo Aula Medica S.A. All rights reserved.